Evaluación agronómica del Rhizobium con inoculación y fertilización nitrogenada en una pastura de trébol blanco (Trifolium repens) y ryegrass perenne (Lolium perenne) - Avellaneda Castro, Víctor Alejandro (2007)
The present work was made in the county of Pichincha, canton Cayambe, parish Cangahua, in the property Yacutigrana, located to a Longitude 78° 10' 30 '' and Latitude 0' 00' 20', average of precipitation 750 mm. Temperature average 13 ºC; and to an altitude 3400 m. The factor in study was: the agronomic evaluation of the Rhizobium with inoculation and fertilization nitrogenada in a Dutch clover pasture (Trifolium repens) and perennial Ryegrass (perennial Lolium) in the high area of Cangahua. Before carrying out the rehearsal it was carried out an equalization cut, next was carried out maintenance fertilization.